Inventorying The Most Common Broccoli Pest Insect and Assessing the Effectiveness of Sticky Traps in Reducing Damage (NTU Journal of Agriculture and Veterinary Science, 2022)
Broccoli (Brassica oleracea) is a cool-season crop that can be grown year-round under controlled conditions such as greenhouses. And the results showed that it was attacked by many pests causing direct damage to crops. As cabbage grey aphid, cabbage white butterfly, great white butterfly, diamondback moths, and cabbage cutworm, and using stick traps have efficient in controlling the density of pests and can be applied within the integrated pest control, so their use avoids damage to the crop. The trap was significant and superior in monitoring and recording the first appearance of the insect pest, as well as in the effect on the quantity and quality of the product obtained, where the highest production was recorded, amounting to approximately 1200kg/greenhouse and the absence of the need to use chemical pesticides for control compared to the control (without traps), where the production reached 700 kg/ greenhouse.